The Role of Islamic Policy Values in the Hospitality Sector: A Comparative Study of Conventional and Sharia Hospitality in Sumedang Regency - Nababan, Chantika Salsabila; Nurhayati, Ima; Putri, Shelyna Mardiana; Anci, Sou; Hidayani, Valentina; Supriyadi, Tedi (Lembaga Yasin AlSys, 2025)
This study compares conventional and Sharia-compliant hotels in Sumedang Regency, with a focus on the application of Islamic values within the hospitality sector. The research aims to analyze how the integration of Sharia principles influences hotel operations and customer satisfaction. Utilizing a qualitative approach, data were collected through interviews and observations at selected hotels. Sharia-compliant hotels adhere to Islamic guidelines by providing halal food, designated prayer facilities, gender-segregated amenities, and marriage verification at check-in. These practices foster trust and enhance satisfaction among Muslim guests. In contrast, conventional hotels emphasize general guest comfort without prioritizing religious considerations and often encounter difficulties in consistently applying Islamic values. The findings indicate that aligning hospitality services with Sharia principles not only enhances competitiveness but also strengthens customer loyalty. This alignment supports the moral and spiritual well-being of Muslim travelers and contributes to the advancement of halal tourism. The study underscores the potential of Sharia-compliant hospitality to offer culturally and religiously sensitive services that meet the growing demands of the Muslim travel market.